Efektifitas Penggunaan Sistem Mentoring Dalam Meningkatkan Kualitas Perawat Di Rumah Sakit - Nita, Yureya; Devita, Yeni; Kristanti, Martina Sinta; Junadhi, Junadhi; Puswati, Desti (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of the use of the Mentoring system in helping nurses to improve the quality of nurses in hospitals. The method used is analytical survey research using a cross sectional approach. The results of the study showed that the effectiveness of the mentoring system (82.5%), satisfaction with the mentoring system (76.6%), the usefulness in improving the Competence of Nurses (77.5%), and the technology and accessibility of the mentoring system (70%). It was concluded that the Mentoring System was more than 76% effective in improving the quality of nurses in hospitals. Keywords: Nurse Quality, Mentoring, Mentor